Fostering well-being and belonging among international graduate students: A positive psychology approach - Hsieh, Chi-Jia; Watson, Sunnie (Journal of International Students, 2025)
International students often feel less belonging and well-being due to adapting to new life and culture. Positive psychology has been widely used to enhance individuals’ well-being and resilience. Previous research has applied positive psychology interventions in various contexts. However, few studies have explored the possibility of implementing positive psychology interventions to support international students’ well-being and belonging. Therefore, this study is designed to help international students in the U.S. develop well-being and a sense of belonging through positive psychology reflection activities. Nine international students completed the surveys, orientation, and 4-week weekly reflection activities, and 8 also completed the optional interviews. The results demonstrated an increase in psychological well-being and the general belongingness score. The participants reported positive attitudes through surveys and interview responses. Future research and implications are suggested.